Anti-biofilm activity of zinc oxide and hydroxyapatite nanoparticles as dental implant coating materials. Issue 12 (December 2015) - Abdulkareem, Elham H.; Memarzadeh, K.; Allaker, R.P.; Huang, J.; Pratten, J.; Spratt, D.
Graphical abstract: Abstract: Objectives: Dental implants are prone to failure as a result of bacterial biofilm accumulation. Such biofilms are often resistant to traditional antimicrobials and the use of nanoparticles as implant coatings may offer a means to control infection over a prolonged period. The objective of this study was to determine the antibiofilm activity of nanoparticulate coated titanium (Ti) discs using a film fermenter based system. Methods: Metal oxide nanoparticles of zinc oxide (nZnO), hydroxyapatite (nHA) and a combination (nZnO + nHA) were coated using electrohydrodynamic deposition onto Ti discs. Using human saliva as an inoculum, biofilms were grown on coated discs for 96 h in a constant depth film fermenter under aerobic conditions with artificial saliva and peri-implant sulcular fluid. Viability assays and biofilm thickness measurements were used to assess antimicrobial activity. Results: Following 96 h, reduced numbers of facultatively anaerobic and Streptococcus spp. on all three nano-coated surfaces were demonstrated. The proportion of non-viable microorganisms was shown to be higher on nZnO and composite (nZnO + nHA) coated surfaces at 96 h compared with nHA coated and uncoated titanium. Biofilm thickness comparison also demonstrated that nZnO and composite coatings to be the most effective. Conclusions: The findings support the use of coating Ti dental implant surfaces with nZnO to provide an antimicrobial function. Clinical significance: Current forms of treatment for implant associated infection are often inadequate and may result in chronic infection requiring implant removal and resective/regenerative procedures to restore and reshape supporting tissue. The use of metal oxide nanoparticles to coat implants could provide osteoconductive and antimicrobial functionalities to prevent failure.